SOFIE project – 3D shaking table test on a seven‐storey full‐scale cross‐laminated timber building‡. (23rd May 2013) - Ceccotti, Ario; Sandhaas, Carmen; Okabe, Minoru; Yasumura, Motoi; Minowa, Chikahiro; Kawai, Naohito
SUMMARY: Multi‐storey buildings made of cross‐laminated timber panels (X‐lam) are becoming a stronger and economically valid alternative in Europe compared with traditional masonry or concrete buildings. During the design process of these multi‐storey buildings, also their earthquake behaviour has to be addressed, especially in seismic‐prone areas such as Italy. However, limited knowledge on the seismic performance is available for this innovative massive timber product. On the basis of extensive testing series comprising monotonic and reversed cyclic tests on X‐lam panels, a pseudodynamic test on a one‐storey X‐lam specimen and 1D shaking table tests on a full‐scale three‐storey specimen, a full‐scale seven‐storey building was designed according to the European seismic standard Eurocode 8 and subjected to earthquake loading on a 3D shaking table. The building was designed with a preliminary action reduction factor of three that had been derived from the experimental results on the three‐storey building. The outcomes of this comprehensive research project called 'SOFIE – Sistema Costruttivo Fiemme' proved the suitability of multi‐storey X‐lam structures for earthquake‐prone regions. The buildings demonstrated self‐centring capabilities and high stiffness combined with sufficient ductility to avoid brittle failures. The tests provided useful information for the seismic design with force‐based methods as defined in Eurocode 8, that is, a preliminary experimentally based action reduction factor of three was confirmed. Valid, ductile joint assemblies were developed, and their importance for the energy dissipation in buildings with rigid X‐lam panels became evident. The seven‐storey building showed relatively high accelerations in the upper storeys, which could lead to secondary damage and which have to be addressed in future research. Copyright © 2013 John Wiley & Sons, Ltd.